Effects of Low Level Water-soluble Pentosans, Alkaline-extractable Pentosans, and Xylanase on the Growth and Development of Broiler Chicks - Q. K. Sheng; L. Q. Yang; H. B. Zhao; X. L. Wang; K. Wang (Asian-Australasian Journal of Animal Sciences, 2013)
This study investigated the effects of low levels of water-soluble pentosans (WSP), alkaline-extractable pentosans (AEP), and xylanase on the growth and organ development of broiler chicks. Three hundred and fifty 1-d-old female broiler chicks were randomly allocated into seven experimental groups of five pen replicates, with ten chicks per replicate. The control group consumed a corn-soybean meal-based diet. Six dietary treatment groups consumed the basal diet supplemented with one of the following: WSP at 50 mg/kg (WSP50) or 100 mg/kg (WSP100); AEP at 50 mg/kg (AEP50) or 100 mg/kg (AEP100); or xylanase at 3 mg/kg (Xase3) or 6 mg/kg (Xase6). Data including the body weight, digestive organ weights, gut length, rectal digesta viscosity, and gut microflora and pH were collected on d 5, 10, and 15. When compared to the control group, WSP50 promoted body weight gain and organ growth throughout the study, calculated as 3-d averages (p<0.05). WSP100 increased weight gain and enhanced organ development (proventriculus, gizzard, and gut) on d 10 (p<0.05), but the 3-d averages were not different from the control group except for the weight of gizzard. Both Xase3 and Xase6 increased the 3-d average weight gain and the growth of the gizzard (p<0.05). WSP50 increased the digesta viscosity compared to Xase3 on d 10 and 15 (p<0.05). WSP50, Xase3, and Xase6 increased the concentration of Lactobacillus in the rectum when compared to the control group (p<0.05), but only Xase3 lowered the digesta pH in the ileum and cecum on d 10 and 15. AEP had minimal influence on the growth and organ development of broilers. The results showed that low levels of WSP, AEP, and xylanase had different effects and underlying mechanisms on the growth and organ development of broiler chicks. WSP50 could increase the growth performance of broilers fed a corn-soybean meal-based diet.